Energy harvesting pavements using air convection - Chiarelli, Andrea (2016)
Pavements are one of the most important components of modern civil infrastructure systems. Being constantly exposed to weather conditions, pavements may be subject to heating and cooling cycles, which vary as a function of the location and are proven to reduce the lifespan and reliability of our transport infrastructure. The most extreme effects of weather are generally seen in the form of overheating of the paving materials or freezing of the pavement surface. In this Thesis, natural convection of air is considered as a means to harvest heat from pavements during hot periods and to provide heat to them when the weather is cold. In the research presented, a buoyancy-driven air flow is allowed through metal pipes installed under an asphalt wearing course. The analysis of the phenomena at work is performed from an experimental, computational, and theoretical point of view. The main contribution to research provided by this Thesis it that the experiments performed show that a convection-powered air flow can be effectively used for the reduction or increase of pavement temperatures up to about 5°C. Moreover, the effects of variations in the design of energy harvesting pavements are quantified and discussed, proving that the installation of all pipes in a single row under the wearing course of a pavement is the overall best solution for the implementation of this technology. Finally, CFD simulations suggest that the air pores that are naturally present in asphalt mixtures are not suitable to allow the air flow required for convection-powered energy harvesting, due to both fluid-dynamic and practical reasons.